Predict the Lifetime for (15.75 kV/400 kV) Transformers Oil of NASIRIYAH Power Plant (University of Thi-Qar Journal for Engineering Sciences, 2019)
The Nasiriyah thermal power plant considered to be within the aging stations of the Iraqi electric power grid which reflected on the performance of operating transformers. Recently, several cases of repeated transformer damage have been reported, which reinforce the need to investigate the causes behind that since the transformer ultimate importance in reliable power supplies for the consumers. As a result of that a priority of investigation have grown to calculate the remaining default life of transformer oil due to its vital role in the processes of insulation and cooling.In this work, the lifetime for transformer oil of the Nasiriyah thermal power plant (15.75 kV/ 400 kV) four transformer that are similar in specification and different in loading values has been investigated. Some oil samples was drawn from the oil used in each transformer in order to conduct measuring tests of variables values (flashpoint, breakdown voltage, viscosity, acidity). All tests have been carried out at high voltage and chemical laboratories. The obtained result showed a widely change in the acidity values, coupled with its entry into bad oil classification, while it shows acceptable change with standard specification for remaining variables. An acidity limit of (0.3 mg KOH/g oil) has been recorded as a major variables to calculate oil lifetime according to the international (IEC-296) standard. Technique for acceleration test has been developed and employed to develop oil lifetime equation by testing the oil samples in high varying temperatures (130 °C, 140 °C, 150 °C) with continuous monitoring of the acidity limit.The obtained results show the validity of these proposed equations to calculate the oil lifetime after their compliance with the four transformer loading rates. The results also show a presence of a serious decline in oil life time at the prevailing operating temperatures for all transformers especially for the highest load rate transformer (AT4) for range between (50 °C- 60 °C). For example, the lifetime prediction of transformer (AT4) a temperature of 60 °C is 3.5 years. A set of recommendations are suggested in order to evade transformer failure. It has been concluded that the oil used in transformer (AT4) should be replaced. Extra oil should be added to (AT1, AT2, AT3) transformers.